2012
DOI: 10.1111/1440-1681.12025
|View full text |Cite
|
Sign up to set email alerts
|

[Nle3,d‐Phe6]‐γ2‐melanocyte‐stimulating hormone possesses the renal excretory but not the cardiovascular actions of the native γ2‐melanocyte‐stimulating hormone in anaesthetized rats

Abstract: The present study compared the cardiovascular and renal actions of γ(2) -melanocyte-stimulating hormone (γ(2) MSH) with those of the synthetic analogue [Nle(3) ,d-Phe(6) ]-γ(2) MSH (NDP-γ(2) MSH) and explored the effects of high dietary salt intake on the renal actions of NDP-γ(2) MSH. Both peptides were infused systemically (3-1000 nmol/kg) and intrarenally (500 fmol/min) into innervated and renally denervated rats fed either a normal (0.4% NaCl) or high-salt (4% NaCl; HS) diet. Mean arterial pressure (MAP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The α1‐adrenergic receptor agonist, phenylephrine, was infused directly into the cortical/medullary interstitium, which was an approach used previously (Cope et al . , O'Neill et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The α1‐adrenergic receptor agonist, phenylephrine, was infused directly into the cortical/medullary interstitium, which was an approach used previously (Cope et al . , O'Neill et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies were undertaken to examine the role of catecholamines in the regulation of fluid reabsorption and NHE3 content of proximal tubular brush border membranes. The a1-adrenergic receptor agonist, phenylephrine, was infused directly into the cortical/medullary interstitium, which was an approach used previously (Cope et al 2013, O'Neill et al 2013. Intrarenal infusion of phenylephrine at the highest rate reduced UV, UNaV and FeNa without significantly altering GFR, suggesting that activation of tubular a 1 -adrenoceptors triggered increased sodium and water absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are conflicting views about the expression of melanocortin receptor subtypes in the kidney [12,15], supportive evidence for the MC3-R based mechanism came from studies showing that protein for MC3-R is present in the rat kidney and that the expression of MC3-R becomes upregulated when rats are fed with a high sodium diet [16,17]. Furthermore, these studies demonstrated that γ-MSH, which is the natural ligand for the MC3-R, stimulates cAMP formation in cultured inner medullary collecting duct cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present finding that the diuretic and natriuretic actions of NDP-α-MSH were reversible with SHU9119 lends support to this concept. Controversy still remains concerning the role of renal nerves in the natriuretic response, since renal denervation was previously found to prevent the natriuretic response to γ-MSH infusion [19], but Cope et al did not observe such an effect [16]. Although the renal MC3 receptors seem to play a pivotal role, the exact mechanism and site of action of melanocortin-evoked natriuresis are still unknown.…”
Section: Discussionmentioning
confidence: 99%